2004
DOI: 10.1677/joe.1.05788
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor regulates proliferation and differentiation of epithelial monolayers derived from islets of postnatal rat pancreas

Abstract: Hepatocyte growth factor (HGF) has been suggested to be a potent regulator of -cell function and proliferation. The purpose of this study was to investigate whether HGF could regulate the proliferation and differentiation of islet-derived epithelial monolayers into insulin-producing cells. We have generated islet-derived epithelial monolayers that are enriched with cells expressing c-Kit, a tyrosine kinase receptor and putative marker, from isolated postnatal rat islets. Monolayers were cultured on type I coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…The HGF concentration used in this assay (50 ng/ml) is known to induce cell proliferation in different cell systems (Wang et al, 2004). Thus, we wondered whether HGF could exert other functions in this system in addition to the promigratory effect.…”
Section: Discussionmentioning
confidence: 99%
“…The HGF concentration used in this assay (50 ng/ml) is known to induce cell proliferation in different cell systems (Wang et al, 2004). Thus, we wondered whether HGF could exert other functions in this system in addition to the promigratory effect.…”
Section: Discussionmentioning
confidence: 99%
“…Third, an alternative explanation is that HGF acts as a physiological suppressor of ␤-cell differentiation, and its absence permits increased generation of new ␤-cells. This seems unlikely because: 1) HGF action would be deleted only in differentiated ␤-cells because we used the RIP promoter for these studies, and it should not be deleted from ␤-cell precursors before they express insulin (45); 2) HGF overexpression in transgenic mice results in a small but significant increase in islet number (20); and 3) HGF has been shown to induce in vitro the differentiation of pancreatic acinar and islet-derived epithelial cells into insulin-expressing cells (32,46). Finally, it is possible that the decreased ␤-cell function and diminished glucose tolerance in MetCKO mice induce compensatory ␤-cell neogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies showed that HGF promotes beta cell proliferation with the support of a fibrin matrix [97]. Recent studies demonstrated that HGF mediates differentiation of immature cell types into insulin-expressing cells [98]. Together, the above data suggests that GLP-1, exendin-4, FGFs, BTC and HGF are useful to promote neogenesis of beta cells from the progenitor cells inside the islets and pancreatic ductal cells.…”
Section: Regulation Of Expansion and Differentiation Of Pancreatic Stmentioning
confidence: 92%